Appropriate properties of carbon nanotubes for the three-dimensional current collector in lithium-ion batteries. (March 2023) - Kaneko, Kentaro; Li, Mochen; Noda, Suguru
Abstract: Carbon nanotubes (CNTs) configured as sponge-like paper can be used as lightweight three-dimensional electrodes for high-energy-density lithium-ion batteries without the need for binders or metal foils. Here, we report on the appropriate structural properties of CNTs for application in lithium-ion battery electrodes. Negative and positive electrodes were fabricated by capturing active materials (graphite and lithium cobalt oxide) with a content of 97 mass% within a self-supporting CNT matrix. The properties of the CNT-based electrodes significantly depend on the specific surface area (SSA) and length of the CNT raw material. Large SSA and length enhance the self-supporting ability of the CNT paper while providing electrically conductive pathways to the active materials. However, an excessively large SSA induces a surplus irreversible capacity on the negative electrode. A relatively small SSA of ∼300 m 2 g –1 and a CNT length greater than several tens of micrometers are appropriate for both the negative and positive electrodes based on the CNT sponge-like architecture. Graphical abstract: Image, graphical abstract